Design and fabrication of a partial flow dilution tunnel for particulate mass sampling in an ethanol blended CI engine. Issue 1 (1st July 2022) - Kumar, Atul; Sahu, Tomesh Kumar; Shukla, Pravesh Chandra
Abstract: Diesel engine is mostly preferred engine especially for heavy duty work, as it delivers high efficiency, durability and low operating cost. Oxides of nitrogen (NOx) and particulate matter (PM) are the main emission components emitted from these diesel engines. Alcohols or biodiesels blending with mineral diesel are known to reduce the NOx and PM emissions. Ethanol fuel contains 35% (m/m) of oxygen, which helps to minimise the smoke and PM emissions. The primary objective of this work is to in-house design and fabricate a partial flow dilution tunnel for PM sampling on substrates. Ethanol blends (E05 and E10; v/v) were tested for Particulate matter collection for a twin cylinder CRDI Compression Ignition Engine. Ethanol blends showed 33% reduction in PM emission compared to mineral diesel.